TINJAUAN YURIDIS PERALIHAN HAK MILIK ADAT PAKPAK MELALUI JUAL BELI DI KECAMATAN SALAK (STUDI PADA KECAMATAN SALAK KABUPATEN PAKPAK BHARAT) - SITTI ROHAYA HASIBUAN (PREMISE LAW JURNAL, 2017)
Land transact in Salak Subdistrict is still done according to the custom; land transact is done before the Village Head, witnessed by the relatives of the seller and the buyer, and by Sukut Nitalun. Land status as a transact object in Salak Subdistrict is an adat land which has been used and cultivated from generation to generation and as an inheritance. The transferred plots of land are wet rice fields, rice fields, and land to be used for housing which have been controlled from generation to generation or from inheritance and from land transfer with buy and sell. Land transact in Salak Subdistrict is usually dine underhandedly; it uses only stamped paper or any paper with stamp and done it before the Village Head. Keywords: Land Transact, Pakpak Community